2019
DOI: 10.1007/s00406-019-01028-7
|View full text |Cite|
|
Sign up to set email alerts
|

Migration and schizophrenia: meta-analysis and explanatory framework

Abstract: Systematic reviews and meta-analyses suggest that there are increased rates of schizophrenia and related psychoses in firstand second-generation migrants and refugees. Here, we present a meta-analysis on the incidence of non-affective psychotic disorders among first-and second-generation migrants. We found substantial evidence for an increased relative risk of incidence among first-and second-generation migrants compared to the native population. As heterogeneity of included studies was high, effect estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 93 publications
(107 reference statements)
3
60
0
4
Order By: Relevance
“…Consequences can include reduced self-esteem, poor adjustment to the new location, and increased rates of depression, phobias, and schizophrenia (e.g. Bennouna et al 2019 , Henssler et al 2020 , Selten et al 2020 ). Unpublished local anecdotes from people previously affected in the Pacific by forced migration from nuclear testing indicate that psychosocial impacts of forced migration can span generations, so corroboration through research methods would be an important task.…”
Section: Mental Health and Wellbeing In Sids Under Climate Changementioning
confidence: 99%
“…Consequences can include reduced self-esteem, poor adjustment to the new location, and increased rates of depression, phobias, and schizophrenia (e.g. Bennouna et al 2019 , Henssler et al 2020 , Selten et al 2020 ). Unpublished local anecdotes from people previously affected in the Pacific by forced migration from nuclear testing indicate that psychosocial impacts of forced migration can span generations, so corroboration through research methods would be an important task.…”
Section: Mental Health and Wellbeing In Sids Under Climate Changementioning
confidence: 99%
“…It can also include homelessness, lack of food and water, xenophobic attacks, poor education, perceived and experienced discrimination, and a high risk of death and injury. [ 4 5 ] Furthermore, social factors, including cultural bereavement, culture shock, social defeat, as well as a discrepancy between expectations and achievement, and acceptance by the new nation can all affect adjustment. [ 3 6 ] Further risk factors in new communities can include social exclusion, stigma, and discrimination.…”
Section: Migration and Mental Healthmentioning
confidence: 99%
“…In a systematic review and meta-analysis, Henssler et al . [ 5 ] suggested that there are increased rates of schizophrenia and related psychoses in first- and second-generation migrants and refugees. The meta-analysis was on the incidence of nonaffective psychotic disorders among first- and second-generation migrants.…”
Section: Migration and Mental Healthmentioning
confidence: 99%
“…Darauf verweisen auch Forschungsergebnisse zu Vorurteilen, Stereotypen und psychischen Belastungen. Vorurteile gegenüber Minoritäten stellen Unterstützung und Solidarität infrage und können dementsprechend zu Diskriminierung und sozialer Isolation beitragen und damit psychische Gesundheit negativ beeinträchtigen [ 6 , 43 ]. Zudem können in sozialen Interaktionen auftretende „ethnische“ und rassistische Stereotype und Vorurteile, die sich gegen Minoritäten richten, zu hohen psychischen Belastungen bei den davon betroffenen Personen führen [ 27 , 42 ].…”
Section: Rassismus Und Diskriminierung – Auswirkungen Auf Wohlbefindeunclassified